2003
DOI: 10.1007/s00228-002-0546-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrarectal pharmacokinetics of two formulations of quinine in children with falciparum malaria

Abstract: Whatever the parenteral formulation of quinine, the blood concentration-time profiles of quinine were similar after intrarectal administration. Intrarectal administration of hydrochloride salt solution is a possible mode of quinine delivery in remote rural areas of Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 8 publications
2
26
1
Order By: Relevance
“…The substitution of the hydrochloride for a gluconate salt and an increase in the pH value to 4.5 improve the local tolerance but may affect the extent of drug distribution (18). The kinetics profiles obtained after intravenous and intramuscular administrations are similar to those previously reported for hydrochloride salt (4,5). In contrast, after rectal administration of 8 mg/kg, the bioavailability of the gluconate form is higher than that previously observed with the more acidic formulations (3,5,6).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The substitution of the hydrochloride for a gluconate salt and an increase in the pH value to 4.5 improve the local tolerance but may affect the extent of drug distribution (18). The kinetics profiles obtained after intravenous and intramuscular administrations are similar to those previously reported for hydrochloride salt (4,5). In contrast, after rectal administration of 8 mg/kg, the bioavailability of the gluconate form is higher than that previously observed with the more acidic formulations (3,5,6).…”
supporting
confidence: 83%
“…The kinetics profiles obtained after intravenous and intramuscular administrations are similar to those previously reported for hydrochloride salt (4,5). In contrast, after rectal administration of 8 mg/kg, the bioavailability of the gluconate form is higher than that previously observed with the more acidic formulations (3,5,6). The main mechanism of rectal absorption is a passive transport that depends mainly on the molecular weight, the lipophilicity, and the degree of ionization of molecules (19).…”
supporting
confidence: 80%
“…The formulation used in both treatment arms was Quinimax (Sanofi-Synthelabo Groupe), which contains 96% quinine, 2.5% quinidine, 0.68% cinchonine, and 0.67% cinchonidine. This was previously demonstrated to have a pharmacokinetic profile that is similar to that of quinine dihydrochloride [8]. For the intrarectal quinine group, the treatment nurse diluted a 500-mg vial of quinine with 13.5 mL of distilled water to obtain a concentration of 30 mg/mL.…”
Section: Participantsmentioning
confidence: 99%
“…Studies of the efficacy of intrarectal quinine in the treatment of cerebral malaria are limited. A few studies in Francophone Africa have reported good clinical efficacy and tolerance of intrarectal quinine [7][8][9][10][11]. Although these studies were randomized trials, they were not blinded and did not use the World Health Organization definition of cerebral malaria as selection criteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation